ANALISIS PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN PAI DI SMA SEKECAMATAN TALIWANG KABUPATEN SUMBAWA BARAT - Toyibi, Dzurriyun; Suhirman, Suhirman; Alkusaeri, Alkusaeri; Setiawan, Yudhi (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
The K-13 curriculum has been implemented since 2013, and the government has adopted a scientific approach to achieve the desired outcomes of the curriculum. However, after ten years of implementing this scientific approach, the learning process and outcomes, including in PAI (Islamic Education), have not shown the expected results. This research aims to: (1) analyze the implementation of the scientific approach in PAI learning in high schools in the Taliwang District, and (2) analyze the supporting factors and barriers to the implementation of the scientific approach in PAI learning in high schools in the Taliwang District. This study is a qualitative research using a narrative inquiry approach. The research was conducted at SMAN 01, SMAN 02, and SMKN 01 Taliwang, with the research subjects being the school principals, PAI teachers, and students. Data were collected through observation, interviews, and documentation using observation sheets, interview guides, and documentation guidelines as instruments. The data were analyzed through data display, data reduction, and verification stages. The results of the study indicate that: (1) the implementation of the scientific approach in PAI learning in high schools in the Taliwang District is carried out in various ways, depending on the availability of media, learning resources, and the creativity of PAI teachers, and (2) the implementation of the scientific approach in PAI learning in SMAN 01, SMAN 02, and SMKN 01 Taliwang is supported by: K-13 training, a good understanding of the scientific approach, lesson plan preparation by PAI teachers, availability of media, learning resources, and the creativity of PAI teachers. However, the implementation of the scientific approach is hindered by factors such as the limited number of PAI class hours, which is only two hours per week, and the lack of enthusiasm among students.